Review of Slum Management Policies in Urban Areas - Ibrohim (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2024)
Urban slum areas in Indonesia began to feel very disruptive to city mechanisms and dynamics in the late 70s, so the government launched Village Improvement programs such as the Moh Slum Improvement Program. Husni Thamrin in Jakarta, Dewi Sartika Village Improvement Program in Bandung, and other village improvements carried out in big cities in Indonesia. While these programs have not been able to solve existing problems, city dynamics are running so fast, especially after reform. The development of cities with very high population pressure is beyond the government's ability to control them. On the other hand, the need for employment and business is very large due to the financial crisis and the phenomenon of job cuts (PHK), because many companies are going bankrupt. This problem must be borne by the city ecosystem which has many limitations. People in every city, because they are pressured by the necessities of life, can do business in urban areas wherever they think there is a chance to live. In this situation, the growth of slum areas in urban areas not only occurs in residential areas, but also occurs in business areas and along road routes which are still possible to use as places of business and residence. Of course, this cannot be tolerated, and the government needs to respond through appropriate policies now and in the future, considering that slum areas are now evenly distributed to all cities in Indonesia and not only in big cities.